(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
An aim of this work is to present the standard indicators of financial analysis, which were published in the Regulation of Minister of Health on economic and financial ratios that are needed to draw up the analysis and forecast of the economic and financial situation of independent public healthcare centers. This is the first regulation, which regulates the evaluation of economic situation through selected indicators of profitability, liquidity, efficiency, and debt of entities operating in the healthcare sector. In the work was conducted presentation of indicators from regulation along with their brief interpretation for healthcare entities. Research methods used in the work are analysis of subject literature on accounting, financial analysis, finances and comparison analysis.